Turnover intention and associated factors among nurses working at governmental hospitals in Bahir Dar city at the time of war, northwest Ethiopia, 2022 - Tena Mekonnen Mihretie; Gebremeskel Kibret Abebe; Hiwote Mulugeta; Abebe Tarekegn Kassaw; Addis Wondmagegn Alamaw; Belaynew Adugna; Firdawek Shenkute Ergetie; Alemu Birara Zemariam (Elsevier, 2024)
Introduction: Turnover intention measures the likelihood that a nurse may soon depart from their current job or that the organization might be considering terminating nurses from their positions. It serves as a reliable predictor of actual turnover. Turnover intention results in deterioration in the standard of nursing care, compromise in patient safety, drop in customer service standards, and inadequate healthcare management. Methods: A cross-sectional study was conducted among 385 nurses employed in three selected government hospitals located in Bahir Dar city, Amhara region. Data collection employed a self-administered questionnaire, with entries managed through EpiData version 4.6 and subsequently transferred to STATA version 14 for coding, cleaning, and analysis. Binary logistic regression was employed to assess the association between dependent and independent variables. Variables with a p-value < 0.05 at a 95 % confidence interval were considered to exhibit statistically significant associations. Result: The findings of this study revealed that 77.7 % of nurses had turnover intention. Multivariable binary logistic regression showed that age (20-27 years) [AOR = 0.36; 95 % CI (0.13, 0.95)], family-to-work conflict [AOR = 2.43; 95 % CI (1.34, 4.41)], salary expectation [AOR = 5.99 (95 % CI: 1.24-27.70)], and job satisfaction [AOR = 5.39 (95 % CI: 1.34-21.64)] were significantly associated with nurses' turnover intention. Conclusion: In this study, the prevalence of turnover intention among nurses working in Bahir Dar governmental hospitals was found to be high. Numerous factors emerged as statistically significant predictors of nurses' turnover intention, encompassing age, salary, and job satisfaction.